The Functions, Roles, and Principles of Islamic Banking in Indonesia: A Review of the Literature - Abd. Rasyid Syamsuri; Handi Gunawan (Journal of Global Islamic Economic Studies, 2023)
An institution of finance called an Islamic Bank has a singular purpose (risalah) and methodology (manhaj), namely the Shariah framework and its tenets drawn from the all-encompassing and universal Islamic Sharia's ethics and values. A significant development in Indonesia's banking industry has been the emergence of Islamic banks, giving customers a choice between using conventional banks or Islamic banks for their financial needs. In light of the fact that Islamic banks operate under the norms of Islamic law using a profit-sharing operational system based on the community principle of al mutanaqisah (a blend of musyarakah and ijarah), while conventional banks utilize an operational interest foregone system (effective interest). Islamic banks use a number of contracts for channeling money, including murabaha, salam, istishna, ijarah, mudlarabah, and musyarakah. Islamic banks also use a number of contracts in their service operations, such as kafalah (bank guarantee), hawalah (debt transfer), sharf (forex buying and selling), and wakalah. Law No. 10 of 1998 Concerning Banking, Law No. 23 of 1999 Concerning Bank Indonesia, Law No. 3 of 2006 as amended by Law No. 50 of 2009 Concerning the Religious Courts, and finally with the issuance of Law No. 21 of 2008 Concerning Islamic Banking, the legal instruments that regulate Islamic banking.